2003
DOI: 10.1055/s-2003-45287
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Prolapsed Chorioamniotic Membrane: Relationship between the Degree of Herniation, Infection, and Pregnancy Prolongation

Abstract: Our objective was to determine the outcome predictor of conservative bed rest therapy for prolapsed chorioamniotic membrane. We could perform tocolysis for 61 women, 41 of visible membrane (group A) and 20 of protruding membrane (group B). The duration of pregnancy prolongation and gestational age (in weeks) at delivery in group A were significantly larger than in group B ( p < 0.05). Outcome of neonates was also significantly different between two groups ( p < 0.05). In 37 women of group A (90%) and 10 of gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Numerous literature reports showed that in most cases this condition evolves within a short time, according to the weeks of gestation, in abortion or PTD [25, 29-31]. Since the fetal prognosis is strictly conditioned and dependent by the gestational age, every attempt possible to prolong the pregnancy is mandatory and must be proposed and pursued with the utmost determination.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous literature reports showed that in most cases this condition evolves within a short time, according to the weeks of gestation, in abortion or PTD [25, 29-31]. Since the fetal prognosis is strictly conditioned and dependent by the gestational age, every attempt possible to prolong the pregnancy is mandatory and must be proposed and pursued with the utmost determination.…”
Section: Discussionmentioning
confidence: 99%